Amplification of microbial DNA from bacterial extracellular vesicles from human placenta - Menon, Ramkumar; Khanipov, Kamil; Radnaa, Enkhtuya; Ganguly, Esha; Bento, Giovana Fernanda Cosi; Urrabaz-Garza, Rheanna; Kammala, Ananth Kumar; Yaklic, Jerome; Pyles, Richard; Golovko, George; Tantengco, Ourlad Alzeus G. (Frontiers in Microbiology, 2023)
The placenta is essential for fetal growth and survival and maintaining a successful pregnancy. The sterility of the placenta has been challenged recently; however, the presence of a placental microbiome has been controversial. We tested the hypothesis that the bacterial extracellular vesicles (BEVs) from Gram-negative bacteria as an alternate source of microbial DNA. Placentae from the term, not in labor Cesareans deliveries, were used, and placental specimens were samples randomly from the fetal side. We developed a protocol for the isolation of BEVs from human tissues and this is the first study to isolate BEVs from human tissue and characterize them. The median size of BEVs was 130–140 nm, and the mean concentration was 1.8–5.5 × 1010 BEVs/g of the wet placenta. BEVs are spherical and contain LPS and ompA. Western blots further confirmed ompA but not human EVs markers ALIX confirming the purity of preparations. Taxonomic abundance profiles showed BEV sequence reads above the levels of the negative controls (all reagent controls). In contrast, the sequence reads in the same placenta were substantially low, indicating nothing beyond contamination. Alpha-diversity showed the number of detected genera was significantly higher in the BEVs than placenta, suggesting BEVs as a likely source of microbial DNA. Beta-diversity further showed significant overlap in the microbiome between BEV and the placenta, confirming that BEVs in the placenta are likely a source of microbial DNA in the placenta. Uptake studies localized BEVs in maternal (decidual) and placental cells (cytotrophoblast), confirming their ability to enter these cells. Lastly, BEVs significantly increased inflammatory cytokine production in THP-1 macrophages in a high-dose group but not in the placental or decidual cells. We propose that the BEVs are normal constituents during pregnancy and likely reach the placenta through hematogenous spread from maternal body sites that harbor microbiome. Their presence may result in a low-grade localized inflammation to prime an antigen response in the placenta; however, insufficient to cause a fetal inflammatory response and adverse pregnancy events. This study suggests that BEVs can confound placental microbiome studies, but their low biomass in the placenta is unlikely to have any immunologic impact.